Estudo da interação genótipo ambiente em búfalos leiteiros do Brasil e da Colômbia - Hurtado Lugo, Naudin Alejandro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was verified the existence of genotype environment interaction (GxE) for traits of economic importance for dairy buffaloes in Brazil and Colombia. A description the problem and the consequences of GxE, and their effect on the genetic parameters in dairy cattle is presented in the first chapter. Moreover, the forms are reviewed to evaluate the effect of GxE, and its relevance to quantitative genetics. In the second chapter was verified the existence of heterogeneity of variances (Hv) for milk yield (MY), fat (FY) and protein (PY) to 270 days of lactation (Y270) in herds in Brazil and Colombia. In analyses reaction norm, the variance components were regressed on the average of MY, FY and PY, adjusted for each class of environmental descriptors (ED) in univariate-traits in animal models. The median estimates of the distributions functions posterior density of variance components and corresponding estimates of heritability and genetic correlations (GC) of Y270, tended to increase as a greater phenotypic standard deviation, and show a scale effect. Estimates of CG, suggested the existence of GxE for MY and PY. However, the GC showed no FY for GxE. Based on the genetic predicted values minimal change was observed in the reclassification of common sires. In conclusion, it is suggested that at the time of selection of animals jointly is necessary to take into account the residual Hv due to its influence on the variance components. In the third chapter was verified the GxE for test-day milk yield (TDMY) for multi-trait analysis in animal models. In the analysis of random regression models (RRM), the variance components of TDMY were regressed to the mean of milk yield to 270 days (MY270) adjusted for each class of ED (high and low level of MY270). The estimated Variance components and heritability for TDMY, were heterogeneous depending of levels MY270. The GC between TDMY were high and positive for adjacent test-days and ...

O objetivo deste estudo foi verificar a existência da interação genótipo ambiente(IGA) para características de importância econômica em bubalinos leiteiros do Brasil e Colômbia. No primeiro capitulo é apresentada uma descrição dos problemas e consequências do efeito da IGA, e seus efeitos sobre os parâmetros genéticos em bovinos leiteiros. Alem disso, são revisados as formas de se avaliar o efeito da IGA, e sua relevância na genética quantitativa. No segundo capitulo foi verificada a existência de heterogeneidade de variâncias(Hv) para a produção de leite(PL), gordura(PG) e proteína(PP) até 270 dias da lactação(P270) em rebanhos do Brasil e Colômbia. Na análise da norma de reação, os componentes de variâncias foram regredidos sobre a média da PL, PG e PP, ajustada para cada classe dos descritores ambientais (ED) em análises uni-características em modelos animais. As estimativas médias das distribuições das funções de densidade a posteriori dos componentes de variância e estimativas de correlação genética (CG) e herdabilidade das P270, tenderam a aumentar conforme maior o desvio-padrão fenotípico, e evidenciaram efeito de escala. As estimativas de CG, indicaram a existência de IGA para PL e PP. Entretanto, as CG para PG não evidenciaram IGA. Com base nos valores genéticos preditos foi observado minima alteração na reclassificação dos reprodutores em comum. Como conclusão sugerese que no momento da seleção dos animais de forma conjunta é necessário levar em conta a Hv residual devido a sua influencia sobre os componentes de variância. No terceiro capitulo foi verificado o efeito de IGA para a produção de leite no dia do controle(PLDC) mediante análises multi-característicos em modelos animais. Na análise dos modelos de regressão aleatória(RRM), os componentes de variância das PLDC, foram regredidos sobre a média da produção de leite até 270 dias da lac- tação (PL270) ...
Keywords: Bufalo; Leite - Produção; Bovino de leite; Legendre, Polinomios de; América do Sul; Milk